Internal current return path for ground leakage current mitigation in current source inverters - Lorenzani, Emilio; Migliazza, Giovanni; Immovilli, Fabio; Gerada, Chris; Zhang, He; Buticchi, Giampaolo (Institute of Electrical and Electronics Engineers, 2019)
This paper analyzes in detail the effect of a simple solution for ground leakage current mitigation applicable to transformerless three-phase current source inverter (CSI). The circuit modification solution is assessed for both traditional CSI topology and for CSI with an additional seventh switch, in literature named CSI7 (or H7), in particular with the splitting of the dc input inductance. In the present work, the solution is applied to grid-connected converters for string photovoltaic applications: scope of the circuit modification is to provide an internal return path from the wye connected capacitors of the output CL filter. This additional return path is able to significantly reduce the ground leakage current without adversely affecting THD. The performance of the proposed solution is assessed by the numerical simulations in case of a string of photovoltaic (PV) modules and the different behavior of CSI and CSI7 topologies is thoroughly investigated. Furthermore, the definition of V-{cmZC} is assessed by applying it to the common mode equivalent circuits for CSI7 with additional return path and their validation by means of a two-step simulation. The simulation results and experimental validation shows good agreement and confirm that the proposed solution is able to strongly reduce the ground leakage current. © 2013 IEEE.